Marriage with a deceased wife's sister. Speech in the House of Commons, April 21st, 1869 on moving the second reading of the marriage bill (Seeleys, 1870)
Repr.: Hansard's Debates. In: Facts and opinions tending to show the scriptural lawfulness of marriage with a deceased wife's sister ...